2014
DOI: 10.1590/1806-9282.60.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate in patients with type 2 diabetes mellitus

Abstract: Objective: to estimate the glomerular filtration using the Cockcroft-Gault (CG), Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations, and serum creatinine in the screening of reduced renal function in patients with type two diabetes (T2DM) enrolled in the Family Health Strategy (ESF, Brazilian federal healthcare program). Methods: a cross-sectional descriptive and analytical study was conducted. The protocol consisted of sociodemographics, phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
4
7
1
5
Order By: Relevance
“…As for risk factors, this study found a significant association between older age group (>50 years), and KD. This is consistent with findings from other studies [6,9,11,12]. It was reported that eGFR will decline gradually with age and at the age >50 years whatever the equations were used; 25% of the diabetics will have eGFR <90 mL/min [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As for risk factors, this study found a significant association between older age group (>50 years), and KD. This is consistent with findings from other studies [6,9,11,12]. It was reported that eGFR will decline gradually with age and at the age >50 years whatever the equations were used; 25% of the diabetics will have eGFR <90 mL/min [17].…”
Section: Discussionsupporting
confidence: 91%
“…Our prevalence estimate of KD was lower than 86.3% reported in Jamaica [9] and 82.6% in Kenya [11], but higher than that of 25.3% reported in Brazil [12] and 27.9% in Spain [13]. These differences in KD prevalence might be because of the differences in case difference in creatinine assays and calibration or due to the use of Cockroft-Gault equation for estimation of GFR could also have led to an underestimation of GFR & thus a higher prevalence of KD.…”
Section: Discussioncontrasting
confidence: 87%
“…The ACR was calculated as albumin (mg)/creatinine (g). Estimated GFR (eGFR) was calculated using the MDRD equation [15]. Glucose levels were determined by enzymatic methods in plasma samples.…”
Section: Subjects and Examinationmentioning
confidence: 99%
“…However, this method requires urine samples and could show altered results due to collection errors. In clinical practice, measuring of plasma creatinine has been most-used the method to assess kidney function, however it alone is not a sensitive method to assess asymptomatic patients with chronic kidney disease (CKD) (Fontela et al, 2014). Instead, eGFR is the most feasible clinical measure of kidney function (KDIGO, 2013).…”
Section: Introductionmentioning
confidence: 99%